Patient-, implant- and prosthetic-related factors on peri-implant mucositis and bone loss - NÍCOLI, Lélis Gustavo [UNESP] (2024)
Peri-implant diseases, including peri-implant mucositis (PIM) and peri-implantitis, are a chronic inflammatory disorder triggered by bacterial biofilm in susceptible hosts. Potential risk factors for peri-implant diseases include smoking, dental plaque accumulation, poor oral hygiene, genetics, and absence of peri-implant keratinized mucosa. This cohort study aimed to evaluate the influence of patient-, implant-, and prosthetic-related factors on PIM and peri-implant bone loss (PBL) around dental implants after 1 year of loading. A total of 54 subjects (22 males and 32 females) were included in the study. Peri-implant clinical parameters were assessed and standardized periapical radiographs of each dental implant were obtained 15 days after the definitive prosthesis installation (baseline) and at 3, 6, and 12 months of follow-up. A total of 173 implants were evaluated. PIM affected 44.8% of the implants and no significant association was found between the investigated parameters and PIM incidence, except for type of implant connection. A significantly higher incidence of PIM (80.0%) was observed for implants with internal hexagon connection type after 1 year of follow-up (p = 0.015). Moreover, a mean PBL of 0.35 ± 1.89 mm was observed and no dental implant was affected by peri-implantitis after 1 year of function. No specific influence of patient, implant, or prosthetic factors on PBL was observed. No association was found between the occurrence of PIM/PBL and the patient-, implant-, and prosthetic-related factors investigated in this cohort study, except for the type of dental-implant connection.